2019
DOI: 10.12968/bjom.2019.27.2.77
|View full text |Cite
|
Sign up to set email alerts
|

Postpartum psychosis and management: a case study

Abstract: Postpartum (or Puerperal) Psychosis (PP) is an acute mood disorder requiring close specialist care. It is a disorder little understood and rare in its occurrence but with devastating consequences. This work retrospectively describes the case study of a 26 year old woman who suffered postpartum psychosis following the birth of her first child. A critical appraisal of the care received follows this, focusing specifically on the postnatal period where she was most affected. It was found that critical information … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Research on postpartum women has identified a wide range of clinical conditions that may impact on their well-being following childbirth: from the more common baby blues, that is a physiological and transitory condition (Rezaie-Keikhaie et al, 2020), to more severe conditions, such as anxiety and mood disorders, puerperal psychosis, and post-traumatic stress disorder (Paulson and Bazemore, 2010;Meltzer-Brody et al, 2017;Mohamied, 2019;Pellowski et al, 2019). Specifically, the prevalence of anxiety spectrum disorders has been found to be around 10% (15% for anxiety symptoms) (Dennis et al, 2017), whilst depressive symptoms have been reported in 10-22% of mothers, depending on the different cut-off scores used in the studies (Zaers et al, 2008;Pampaka et al, 2018;Sunnqvist et al, 2018).…”
Section: Psychological Well-being Of Postpartum Womenmentioning
confidence: 99%
See 1 more Smart Citation
“…Research on postpartum women has identified a wide range of clinical conditions that may impact on their well-being following childbirth: from the more common baby blues, that is a physiological and transitory condition (Rezaie-Keikhaie et al, 2020), to more severe conditions, such as anxiety and mood disorders, puerperal psychosis, and post-traumatic stress disorder (Paulson and Bazemore, 2010;Meltzer-Brody et al, 2017;Mohamied, 2019;Pellowski et al, 2019). Specifically, the prevalence of anxiety spectrum disorders has been found to be around 10% (15% for anxiety symptoms) (Dennis et al, 2017), whilst depressive symptoms have been reported in 10-22% of mothers, depending on the different cut-off scores used in the studies (Zaers et al, 2008;Pampaka et al, 2018;Sunnqvist et al, 2018).…”
Section: Psychological Well-being Of Postpartum Womenmentioning
confidence: 99%
“…The birth of a child represents a critical experience in a woman's life, entailing several changes both at the individual (physical and psychological) and interpersonal level (Lawrence et al, 2008;Guzzo and Hayford, 2020). This experience may negatively impact on individual well-being, leading to several forms of distress and/or diseases including anxiety, mood and post-traumatic stress disorders (Paulson and Bazemore, 2010;Meltzer-Brody et al, 2017;Mohamied, 2019;Pellowski et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The birth of a child significantly impacts a women's psychological well-being and may lead to several forms of diseases, ranging from baby blues to more severe conditions such as anxiety disorders, depression, puerperal psychosis, and post-traumatic stress disorders [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Inpatient care, ideally within a Mother and Baby Unit (MBU; Gillham and Wittkowski 2015) and pharmacological intervention, is almost always required (NICE 2018;Jones and Smith 2009). Family members are reported to be integral during this process and should be involved in care and treatment planning (Engqvist and Nilsson 2014;Mohamied 2019).…”
Section: Introductionmentioning
confidence: 99%